Analysis of Students' Cognitive Abilities Based on Gender and Learning Style - Bayyinah Rismawati; Hadi Kusmanto; Hendri Handoko (EduMa: Mathematics education learning and teaching, 2025)
This study aims to determine the differences in students' cognitive abilities based on gender and the influence of learning styles on cognitive abilities. Using a quantitative method with a One Shot Case Study design, the study involved 40 students of grade VIII MTsN 2 Cirebon. Data were collected through questionnaires and tests, then analyzed descriptively, sample independent t-tests, and simple linear regressions. The results showed that there was a difference in the average cognitive ability between male and female students. The average score of male cognitive ability is 85% and is in the high category. The average cognitive ability of students with visual, auditory, and kinesthetic learning styles is in the moderate category of around 65-66%. In addition, auditory learning styles have the highest influence on students' cognitive abilities, followed by visual and then kinesthetic learning styles.